Transport Network Vehicle Service Core II: (Booking, GPS, Payment, Storeroom Management, Transport Analytics): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Transport Network Vehicle Service allows passengers to connect and book online. It canprovide an alternative public transport system in terms of premise or appeal niche. Core II withsubmodules: GPS, Booking, Payment, Storeroom Management, Transport Analytics. Thisstudy begins with the process of the system, the explanation of the problem experienced usingthe identical method, the goals of the proposed system, and the benefits of the proposedsystem for the user. Core II focuses on the Driver and Passenger and their respectiveinformation and data.This project will enhance the procedure and speed up the transactions and tracking in thesystem due to technology use. The developers can improve existing operations. With a tap ofthe hand, you can track and pick up the service transactions related to the system. The Core IIof TNVS is obliged to ensure the security of the system and track the driver and passengers.The essential policy is to organize bookings and to track them productively. The Core II ofTNVS can manage the payments and booking for the passengers in the designatedreservations to guide both passengers who book them.The demand for convenient operation of the Core II condition of Transport Network VehicleService (TNVS) has appeared in the higher popularity of carpooling or ridesharing offers andusing of technology to conduct these services. The expansion of demands for the productivemanagement of registrations, insurance, or security, and accounts for the users and drivers.With the introduction of ride-sharing services, Filipinos' mobility underwent a radical change,especially in urban areas. Ride-sharing technology transformed the transportation norm,making it the favored means of transportation for the vast majority of urban Filipino netizenswhen taxis are hard to come by, and trains are packed.
Keywords: IT & Management